ANALISIS KONSEP INSTAGRAMABLE PADA INTERIOR HOTEL LOKAL.id YOGYAKARTA - Niken Laksitarini (LPPM Institut Desain dan Bisnis Bali, 2023)
The hotel is a facility that combines elements of services and products. They are competing in many ways so that the products and services they have can attract more potential customers to come and visit. It is not unusual if the satisfaction of visitors lies in their satisfaction with the services they receive. But before potential customers feel the experience of the services obtained, the allure element can be the first thing done so that potential customers are interested in coming. Instagram as a social media that is quite popular with society today is one of the most promising marketing media for businesses. On this basis the Hotel.id which is located in the city of Yogyakarta seeks to design its interior space by carrying out the concept of instagramable. The choice of colors and composition of shapes on the Kawung Batik motif that has been transformed to become more modern and contemporary is one of the key attractions for visitors, capturing their moments and share their experiences on Instagram as a social media. The method used is a qualitative method. It is hoped that the research results obtained can be a reference in further research for researchers.